Navigating ethical boundaries: Subtle agency and compliance among tech workers in China and the United States - Di Di; Bryce Nishikawa (Big Data & Society)
Tech workers often experience ethical tensions arising from the misalignment of their values and the prevailing unethical or ethically ambiguous practices concerning data and algorithms in the workplace. Despite this, there is an insufficient understanding of how tech professionals address ethical tensions. Based on interviews with 98 tech workers in China and the United States, this study explores ethical tensions, the workers’ responses, and potential cross-national variations. It identifies three prevalent strategies by which tech workers navigate conflicts between their ethical principles and their companies’ practices: complying with market fundamentalism, compromising personal ethics, and upholding and critiquing ethical guidelines. Cross-national differences in strategy implementation highlight nuanced approaches by tech workers in diverse economic, political, and ethical contexts. The study positions these responses within a theoretical framework of ethical agency, revealing tech workers’ subtle ethical agency and the factors that constrain their decision-making processes. It also contributes data-driven insights to promote ethical practices in the global tech industry.